1993
DOI: 10.1021/jm00072a023
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated 2-(5'-salicyl)naphthalenes as protein-tyrosine kinase inhibitors

Abstract: The salicyl group figures prominently in several potent protein-tyrosine kinase (PTK) inhibitors, including the fermentation product lavendustin A (3), the salicylsulfonyl nitrostyryl 30, and our recently reported salicyl-containing stilbene 7. Taking compound 7 and the isomeric 8 as lead structures, bicyclic nuclei 9-12 were prepared as conformationally constrained mimetics in which the hydroxyphenyl rings of 7 and 8 are held coplanar with the stilbene ethylene bridge. A similar approach with styryl-based PTK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…These findings suggested that a high degree of flexibility with regard to the relative spatial positions of the two aromatic ring systems might be important for high antiproliferative activity. Higher flexibility might also be the reason for the superior activity of the (2,5-dimethoxyphenyl)ethyl (12,13) and (2,5-dimethoxybenzyl)oxy (7,8) versus (2,5-dimethoxybenzyl)amino (4,5) analogs. In the benzylamino compounds, a preferred conformational arrangement of the molecule could be expected due to potential interaction of the amino function with the 2-methoxy group.…”
Section: Results and Discussion Of Biological Activitiesmentioning
confidence: 99%
“…These findings suggested that a high degree of flexibility with regard to the relative spatial positions of the two aromatic ring systems might be important for high antiproliferative activity. Higher flexibility might also be the reason for the superior activity of the (2,5-dimethoxyphenyl)ethyl (12,13) and (2,5-dimethoxybenzyl)oxy (7,8) versus (2,5-dimethoxybenzyl)amino (4,5) analogs. In the benzylamino compounds, a preferred conformational arrangement of the molecule could be expected due to potential interaction of the amino function with the 2-methoxy group.…”
Section: Results and Discussion Of Biological Activitiesmentioning
confidence: 99%
“…We followed up these investigations by assessing the effects of a further two drugs, ST638 and lavendustin C. Both of these inhibitors are reported to be more potent against receptor associated tyrosine kinases and will only inhibit src tyrosine kinases at concentrations above 10 M and 18 M respectively [28,29]. In our hands, ST638 (1 to 10 M) caused a significant inhibition of anti-IgE induced histamine release from human basophils.…”
Section: Resultsmentioning
confidence: 94%
“…4 [5a] and 6 [5b] ). In addition, similar non‐aminated analogues like 3 a‐d [5e,h,k] could be accessed either from cross‐couplings [5e,h, ° ,p] or by Wittig‐type [5h,x] reactions. In the field of combinatorial chemistry, a series of anticancer lavendustin analogues linked by a triazole ring ( e. g .…”
Section: Introductionmentioning
confidence: 99%